COMPACT TWO-PORT ANTENNA WITH PARASITIC NOTCH AND DEFECTive GROUND FOR WIRELESS COMMUNICATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
This paper presents a compact multiple input multiple output antenna (MIMO) with a wireless local area network (WLAN) notch characteristic for ultra-wideband (UWB) applications. The two modified rectangular radiators share a common ground that provides UWB response. The design is modeled over FR4 material and has an overall compact size of 0.34 λ0 × 0.24 λ0 × 0.015 λ0 mm3 at the frequency of 2.9 GHz. A tree-shaped decoupling structure with multiple slots in the ground is introduced between the ports to establish good isolation. The open-ended slots in the ground perturb diminish the surface current between two ports and ensure the isolation larger than 20 dB in the entire UWB from 2.9 GHz to 10.2 GHz. An S-shaped parasitic stub is utilized at the backside of the radiating element to implement a band notch characteristic from 5.03 GHz to 5.90 GHz. The proposed antenna is also investigated for wearable applications with a human tissue model showing a small SAR value (less than 1.6 W/kg). The simulated and measured result shows that the designed antenna suits MIMO performance and wearable devices.
Keywords: Multiple input multiple output antenna (MIMO); ); Ultrawideband (UWB); Wireless local area network notch (WLAN); Wearable applications